Entrepreneurship at the limits - Lena Olaison (Copenhagen Business School (CBS), 2014)
This PhD dissertation is based on four published articles. It operates within the processual view of entrepreneurship studies (Steyaert, 1997), which draws on process philosophy to develop research strategies (Sørensen, 2005). The research has been guided by two strategies for understanding entrepreneurship: `moving' (e.g. Steyaert and Hjorth, 2003) and `unveiling' (e.g. Jones and Spicer, 2009). These strategies have so far been pursued largely in the conceptual domain, and this doctoral dissertation is an effort to take them a step further by combining empirical investigation and philosophical reflection. The aim is to investigate how a processual study of entrepreneurship `should be worked out' in practice (Kristensen, Lopdrup-Hjorth and Sørensen, 2014). The first two studies contribute an empirically informed conceptualisation of entrepreneurship, the first focused on how organisations are created, the second providing stories of emerging practices of female entrepreneurs. Though they aim to provide alternative conceptualisations, they remain firmly rooted in `traditional' social science, offering alternative approaches to the dominant understandings of entrepreneurship, and utilizing accepted and traditional methodologies and theories. The last two papers are more experimental in their design. The aim is still to problematize discursive or practical aspects of entrepreneurship and processes around entrepreneurship, but also to investigate alternative methods for creating knowledge. The third study explores the somewhat paradoxical results of SME support schemes and develops a role-play-enhanced focus group technique. The fourth study is based on an organisational ethnography in antiquarian bookshops and experiments with fictional accounts and literary techniques as methods to generate knowledge. The contribution of this dissertation to processual studies in entrepreneurship research is twofold. The first two papers are illustrations of an application of process concepts, while the last two papers illustrate the attempt to create process concepts. Taken together, the studies demonstrate how a processual study of entrepreneurship might be worked out in practice.
hdl:10398/8917
Keywords: 650